Building Cyber-Physical Systems - A Smart BuildingUse Case - Bakakeu Ngassam, Romuald Jupiter; Schäfer, Franziska; Bauer, Jochen; Michl, Markus; Franke, Jörg (Smart Cities: Foundations, Principles, and Applications, 2017)
This chapter explores the concept of smart home and smart building based on internet-of-things (IoT) and cyber-physical system (CPS) technologies. By reviewing the challenges of the smart home vision, it highlights that CPS-based smart environments are best suited to support the integration of heterogeneous devices with different application domains and architectures. To illustrate the concept of a CPS-based smart building installation with self-configuration and self-organization abilities, the chapter presents implementation of smart home use cases based on the paradigms of "Industry 4.0". In addition, it also analyzes and discusses the performance of the implemented prototype. The concept of "Industry 4.0" provides a vision for the application of CPS in industrial automation. The chapter then proposes an approach based on OPC unified architecture (OPC UA) that supports self-description by using a common ontology and self-organization through the use of multi-agent systems (MAS) theory.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Cyber-physical ecosystem; Industrial automation; Internet-of-things; Multi-agent systems theory; OPC unified architecture; Smart building; Smart home use cases

Designing an OPC UA based Ecosystem for Smarter Homes - Schäfer, Franziska; Bakakeu Ngassam, Romuald Jupiter; Kleinert, Bruno; Michl, Markus; Fey, Dietmar; Franke, Jörg (Advanced Engineering Forum 19, 2016)

Die intelligente Wohnung als Baustein im Internet der Dinge: Potenzialanalyse und Konzept einer domänenübergreifenden Lösung - Bauer, Jochen; Kettschau, Anna-Katharina; Michl, Markus; Bürner, Johannes; Franke, Jörg (Erste Transdisziplinäre Konferenz zum Thema Technische Unterstützungssysteme, die die Menschen wirklich wollen, 2014)
Keywords: AAL; E|Home; Energie; Smart Home

Dreidimensionale Planung, Simulation und Überwachung von Produktionssystemen mit VRML - Feldmann, Klaus; Brossog, Matthias; Merhof, Jochen; Michl, Markus (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2008)
Der Einsatz frei zugänglicher und kostenloser Technologien für die Entwicklung von rechnergestützten Werkzeugen zur Unterstützung von Planern, Herstellern und Betreibern von Produktionsanlagen bietet ein großes Potential zur Effizienzsteigerung vor und während des Anlagenbetriebs. Der vorliegende Artikel zeigt mehrere Ansatzpunkte für den gewinnbringenden Einsatz der VRML-Technologie am Lehrstuhl FAPS der Universität Erlangen auf. Angefangen bei der webbasierten Layoutplanung bietet diese Möglichkeit der 3D-Beschreibung ebenso Möglichkeiten für die Umsetzung einer webbasierten Simulation sowie für unterschiedliche Anwendungen zur Zustandsüberwachung im Rahmen eines Diagnosesystems oder für Entwicklungen im Bereich der betriebsbegleitenden Simulation.
Keywords: Planung; Webtechnologien; VRML

Gestaltung einer Fertigungsumgebung für Ladesäulen: Konzeption einer schlanken, ressourceneffizienten und flexiblen Montage - Fauser, Florian; Michl, Markus; Franke, Jörg (wt Werkstattstechnik - Online, 2016)
Due to the increasing significance of electromobility, the need for charging stations rises. To ensure that the growing demand can be met, production has to be adjusted to the new requirements. The production environment has to provide a high rate of flexibility to enable reacting to the development of electromobility. The article describes solutions covering the topics layout and material flow, workplace design and tool management as well as purchasing and warehousing.
CRIS-Team Scopus Importer:2023-03-07

HealthRec - Empfehlungssystem zur Behandlung des metabolischen Syndroms im Smart Home - Bauer, Jochen; Michl, Markus; Kettschau, Anna-Katharina; Wiebe, Sergej; Vierow, Verena; Ge, Mouzhi; Franke, Jörg (Zukunft Lebensräume - Gesundheit, Selbstständigkeit und Komfort im demografischen Wandel Konzepte und Technologien für die Wohnungs-, Immobilien-, Gesundheits- und Pflegewirtschaft, 2016)

Innovative Flexible Heating System by the Use of Additive Plasma Coating Technology: Heating Where Heat Is Needed by Additive Metallization of Furniture and Walls - Braun, Thomas; Bürner, Johannes; Michl, Markus; Schaller, Lukas; Böhm, Ralf; Franke, Jörg (Proceedings of the 4th International Conference on Smart Energy Grid Engineering (SEGE), 2016)

Intelligente Wohnung - Bauer, Jochen; Kettschau, Anna-Katharina; Michl, Markus; Bürner, Johannes; Franke, Jörg (Technische Unterstützungssysteme, 2015)

NutriScale - Key Figures for Daily Food Choices - Bauer, Jochen; Volkhardt, Ina; Michl, Markus; Blumthaler, Christina; Wiebe, Sergej; Rashid, Ria; Franke, Jörg (Advanced Engineering Forum, 2016)

NutriScale - Key Figures for Food Selection - Bauer, Jochen; Michl, Markus; Blumthaler, Christina; Wiebe, Sergej; Rashid, Ria; Franke, Jörg (Proceedings of the German Nutrition Society – Volume 21 (2016), 2016)

Potential Analysis of the Use of Electric Storage Heaters for Demand Side Management Applications - Bürner, Johannes; Braun, Thomas; Gaus, Michael; Michl, Markus; Franke, Jörg (Proceedings of the 4th International Conference on Smart Energy Grid Engineering (SEGE), 2016)

(untitled) - Brossog, Matthias; Michl, Markus (Handbuch Fügen, Handhaben, Montieren)
Die rechnergestützte Planung von Montagezellen ist ein Teilbereich der Digitalen Fabrik, die laut VDI-Richtlinie 4499 als Gesamtheit aller Mitarbeiter, Softwarewerkzeuge und Prozesse, welche zur Erstellung der virtuellen und realen Produktion notwendig sind, definiert wird (VDI 4499). Dieser Ansatz bietet vielfältige Potenziale, die bislang vor allem in größeren Unternehmen mit eigenen Simulationsabteilungen oder von kleineren und mittleren Unternehmen (KMU) unter Beauftragung von Engineering-Dienstleistern ausgeschöpft werden. Weit verbreitet sind auch heute noch die Vorbehalte, wenn es um die Einführung dieser neuen Technologien in Unternehmen geht. Dabei werden meist die hohen Kosten im Vergleich zu einem schwer abzuschätzenden Nutzen als Hauptargument gegen den Einsatz von Methoden der Digitalen Fabrik genannt. Ebenso führen der erforderliche Einarbeitungsaufwand in Verbindung mit der Bereitstellung von qualifiziertem Personal sowie der hohe Modellierungsaufwand vor allem bei 3D-Modellen nicht selten zur Vermeidung rechnergestützter Hilfsmittel. Das immense Potenzial zur Beschleunigung der Prozesse durch Parallelisierung der Produkt- und Produktionsplanung wird bei der Abwägung oft nicht betrachtet. Ziel dieses Beitrags ist es daher, durch Aufzeigen rechnergestützter Methoden samt dazugehöriger Beispiele insbesondere auf die Vorteile eines durchgängigen Einsatzes von Werkzeugen der Digitalen Fabrik bei der Planung von Montagezellen aufmerksam zu machen. Dabei stehen einerseits technische und organisatorische Aufgaben wie die Planung des zelleninternen Materialflusses, der Teilebereitstellung sowie der Handhabung und Speicherung von Bauteilen unter Berücksichtigung der Wirtschaftlichkeit im Fokus. Andererseits wird sowohl auf die Gestaltung manueller Arbeitsplätze und der Arbeitsumgebung nach ergonomischen Gesichtspunkten als auch auf die Besonderheiten bei der rechnergestützten Planung automatisierter Montagezellen eingegangen.
Keywords: Montage; Planung; Entwurf

Smart Energy and Grid: Novel Approaches for the Efficient Generation, Storage, and Usage of Energy in the Smart Home and the Smart Grid Linkup: Foundations, Principles, and Applications - Praß, Julian; Weber, Johannes; Staub, Sebastian; Bürner, Johannes; Böhm, Ralf; Braun, Thomas; Hein, Moritz; Michl, Markus; Beck, Michael; Franke, Jörg (Smart Cities: Foundations, Principles, and Applications, 2017)

User Attitude Toward a Novel Smart Heating System - Kettschau, Anna-Katharina; Michl, Markus (Advanced Engineering Forum, 2016)
Keywords: Smart Home; Technology Use; User Acceptance; Attitudes toward technology

Von der Industrie 4.0 zur Wohnung 4.0 – Einsatzpotenziale verteilter Systemansätze im industriellen und privaten Umfeld - Michl, Markus; Schäfer, Franziska; Bauer, Jochen; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2015)
The paper at hand compares the challenges in pushing the 4th industrial revolution onwards to those of the progressing home automation. Based on this comparison known solutions in the industry respectively home environment are put into relation in order to determine synergies for an efficient joint advancement of both application fields.
Keywords: E|Home

Web-based Engineering Platform for Planning and Simulation of Industrial Plants and Workcells - Brossog, Matthias; Michl, Markus; Franke, Jörg (Proceedings of the 1st International Conference on Through-life Engineering Services, 2012)
The virtualisation of the industrial planning process fostered by the application of state-of-the-art simulation systems improves its efficiency and lowers its risk significantly. Digital factory solutions are getting more and more powerful, but are not adapted to the requirements of small- and medium-sized companies. They need hardware and software independent solutions with integrated functions for essential engineering tasks. A unique data format has to be developed for connecting several standalone software tools and establishing a global communication platform. In the light of this situation FAPS developed a web-based facility planning system focussed on assembly in order to provide the advantages of virtualized planning processes to an expanded community. This framework implies a basic concept for building up an internet-based comprehensive engineering platform.
Keywords: Simulation; Web technologies; Engineering